Determinants of Voluntary Bank Disclosure: Evidence from Japanese Shinkin Banks - Mark M. Spiegel; Nobuyoshi Yamori (Center for Economic Studies and ifo Institute (CESifo), 2004)
Disclosure is widely regarded as a necessary condition for market discipline in a modern financial sector. However, the determinants of disclosure decisions are still unknown, particularly among banks. This paper investigates the determinants of disclosure by Japanese Shinkin banks in 1996 and 1997. This period is unique because disclosure of non-performing loans was voluntary for Shinkin banks at this time. We find that banks with more serious bad loan problems, more leverage, less competitive pressure, and smaller banks were less likely to choose to voluntarily disclose. These results suggest that there may be a role for compulsory disclosure, as weak banks appear to disproportionately avoid voluntary disclosure.
Keywords: 330; disclosure; Japanese banking; market discipline